Streptomyces spp. sebagai Pengendali Hayati Busuk Fusarium pada Bawang Merah: Streptomyces spp. as Biocontrol Agents of Fusarium Basal Rot on Shallots - Eka Wijayanti; Asih Nawangsih, Abdjad; Toding Tondok, Efi (Jurnal Fitopatologi Indonesia, 2024)
Streptomyces spp. as Biocontrol Agents of Fusarium Basal Rot on ShallotsStreptomyces spp. have been widely studied as biological control agents of plant diseases because of their ability to produce various types of antibiotics, especially anti-fungal compounds. Its application to control Fusarium oxysporum f. sp. cepae causes fusarium basal rot disease on shallots in Indonesia has not been explored. The tests carried out included testing the effectiveness of Streptomyces spp. on shallot growth and fusarium basal rot disease incidence, as well as analyzing the compounds produced by Streptomyces spp. The test results show that Streptomyces spp. could not increase the growth parameters. Meanwhile, the application of Streptomyces spp. able to suppress the incidence of fusarium basal rot disease and prolong the incubation period of the pathogen. Analysis of the crude extract of S. lydicus ABF 59 showed that five dominant compounds are antifungal, namely, d-limonene, tridecane, o-cymene, 2,4-di-tert-butylphenol (2,4-DTBP), and hexadecanoic acid, methyl ester.